Aromatherapy in conjunction with physical/occupational therapy in an acute care setting: Early results - A Elizabeth Koyle; Nicole Hofmeister; Rebecca Reding (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2022)
Pain and nausea are common complaints by patients in acute care settings and these symptoms can prevent participation in their physical or occupational therapy sessions. Because mobilization during acute care hospitalization is important for reducing the length of stay, postoperative complications, risk for deep vein thrombosis, pneumonia, and pressure ulcers, implementing non-pharmacological solutions to engage patients in mobilization is worth investigating. It is hypothesized that the use of inhaled essential oils may improve patients' perception of pain and their coping with nausea, enabling a patient to have active participation in physical or occupational therapy. This participation can minimize hospitalization-related risks as well as potentially reduce the length of stay in the hospital. This IRB-approved study is an early feasibility, single-site, randomized, placebo-controlled clinical trial utilizing three essential oils: lavender, mandarin, and peppermint. These oils are administered via an inhalation patch affixed to the chest region of the subject's gown. Perceived pain or nausea levels are assessed before and after the use of aromatherapy during which the subject participates in their planned physical or occupational therapy session. While it is too early to determine the effects of aromatherapy, preliminary results suggest the use of lavender oil may have a positive effect on pain.